1994
DOI: 10.1007/bf02015022
|View full text |Cite
|
Sign up to set email alerts
|

Torsion of an accessory spleen presenting as an acute abdomen with an inflammatory mass

Abstract: Torsion of an accessory spleen is extremely rare. Only seven cases in children have been reported in the literature. This entity should be considered in the differential diagnosis of acute abdomen associated with an intraperitoneal inflammatory mass. This report describes a 10-year-old boy with severe abdominal pain and a mass that was found to be due to infarction of an accessory spleen that had twisted on its pedicle. Magnetic resonance imaging taken at two different times was helpful in detecting an inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
52
1
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 4 publications
0
52
1
1
Order By: Relevance
“…However, an accessory spleen manifesting as a solid intrasplenic pseudotumor has rarely been reported. Previous studies reported an accessory spleen presenting as an inflammatory mass and provided radiologic imaging of splenic abnormalities (2,3,7). In the present study, the case of a male patient who was admitted to The Second Hospital of Shandong University (Jinan, China) presenting with a pseudotumoral accessory spleen is reported.…”
Section: Introductionmentioning
confidence: 81%
See 1 more Smart Citation
“…However, an accessory spleen manifesting as a solid intrasplenic pseudotumor has rarely been reported. Previous studies reported an accessory spleen presenting as an inflammatory mass and provided radiologic imaging of splenic abnormalities (2,3,7). In the present study, the case of a male patient who was admitted to The Second Hospital of Shandong University (Jinan, China) presenting with a pseudotumoral accessory spleen is reported.…”
Section: Introductionmentioning
confidence: 81%
“…An accessory spleen is a normal variant that is typically located at the splenic hilum, but is occasionally noted as a tumor-mimicking lesion located at multiple other sites, including the pelvis or gastrocolic ligament (1), and even the left scrotum (2) or mediastinum (3). Accessory spleens occur in ~10% of the population and are usually located in the region of the splenic helum.…”
Section: Introductionmentioning
confidence: 99%
“…1 Accessory spleens have been reported to mimic gastric SMTs, enlarged lymph nodes, and tumors arising from adjacent organs such as the adrenal gland, pancreas, and kidney. [5][6][7][8][9] Although an accessory spleen is an incidental finding with no clinical significance in most patients, 2,10 they can sometimes become symptomatic due to torsion, spontaneous rupture, hemorrhage and cystic formation. [5][6][7][8] Therefore, detection and characterization can be clinically important, especially in cases such as the present one where the lesion mimicked a gastric SMT.…”
Section: Discussionmentioning
confidence: 99%
“…A diagnosis of accessory spleen manifesting as a gastric SMT was made. As complications associated with an accessory spleen can rarely include torsion of a wandering accessory spleen or bleeding caused by spontaneous rupture [14][15][16][17], the patient is now carefully followed in outpatient clinic.…”
Section: Case Reportmentioning
confidence: 99%
“…It is located at the splenic hilum or adjacent to the pancreatic tail in most cases [3,6] . Although it is usually asymptomatic and incidentally discovered, accessory spleen is clinically important in certain patients [7][8][9][10][11][12][13][14][15][16][17] . It is likely that some accessory spleens simulate tumors arising from adjacent organs such as the kidney, adrenal grand and pancreas [3][4][5][6][7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%